Energy Efficient Homes: Introduction to LED Lighting - Barbara Haldeman; Wendell A. Porter; Kathleen C. Ruppert (EDIS)
FCS-3280, a 4-page illustrated fact sheet by Barbara Haldeman, Wendell A. Porter, and Kathleen C. Ruppert, describes what light emitting diode (LED) lighting is, how it works, how it compares to incandescent, and whether they are a good choice for home lighting. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.